A Holistic Method of Assessing Efficiency and Sustainability in Agricultural Production Systems - Mwambo, Francis Molua; Fürst, Christine (Journal of Environmental Accounting and Management, 2026)
Until now, no single universally adaptable method exits for complete assessment of efficiency and sustainability of agricultural production systems. Existing methods are limited for analyzing agricultural systems. This paper presents the Emergy-Data Envelopment Analysis method; which we built from aggregating Emergy Analysis (EMA) and Data Envelopment Analysis (DEA) into a framework, to provide improved accounting of resource and energy use efficiency including absolute and relative sustainability of agricultural production systems. The method of assessment is as follows. An emergy diagram of the production system is drawn to visually represent the system. Inputs and outputs of the system are estimated on an annual base in their standard physical units of measurement. The available energy content (exergy) of input and output resources are calculated respectively using appropriate methods of calculating exergy for each given input and output. This is done assuming the concept of energy memory. Using Microsoft excel, the emergy of the input and output resources are calculated as the mathematical product of resource exergy and unit emergy value (UEV). The refined procedure of emergy calculation by Brown and Ulgiati (2016) is applied, and it leads to the retainment of selected inputs and outputs of various resource types. The emergies of the selected resource inputs and outputs from comparative peer systems of production (decision making units - DMUs) are concatenated into a table (.csv format), and imported into a model of DEA. The optimization function in DEA applies Pareto efficiency to estimate the relative technical efficiency (rTE) scores among peer units. The score value is a proxy indicator for relative sustainability. The calculated UEV of a product equates to eco-efficiency, and it is applied to evaluate the resource and energy use efficiency. Selected emergy-based indicators of proven reliability are applied for the evaluation of absolute sustainability. The composition of the evaluation outcomes provides improved accounting information that contributes to completeness of assessed efficiency and sustainability of agricultural systems as a whole.